2015
DOI: 10.1002/gcc.22247
|View full text |Cite
|
Sign up to set email alerts
|

MAP2K1 and MAP3K1 mutations in langerhans cell histiocytosis

Abstract: Langerhans cell histiocytosis (LCH) is now understood to be a neoplastic disease in which over 50% of cases have somatic activating mutations of BRAF. However, the extracellular signal-related (ERK) pathway is activated in all cases including those with wild type BRAF alleles. Here, we applied a targeted massively parallel sequencing panel to 30 LCH samples to test for the presence of additional genetic alterations that might cause ERK pathway activation. In 20 BRAF wild type samples, we found 3 somatic mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
126
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 27 publications
9
126
1
1
Order By: Relevance
“…In summary, here we present a case of RDD involving the salivary gland harboring an activating KRAS mutation, suggesting that at least a subset of RDD cases may be clonal processes, which is also consistent with the findings from other recently published work by other authors [31]. Further mutational studies on this rare histiocytic disease should be undertaken to better characterize its pathogenesis as well as open up potential avenues for therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In summary, here we present a case of RDD involving the salivary gland harboring an activating KRAS mutation, suggesting that at least a subset of RDD cases may be clonal processes, which is also consistent with the findings from other recently published work by other authors [31]. Further mutational studies on this rare histiocytic disease should be undertaken to better characterize its pathogenesis as well as open up potential avenues for therapy.…”
Section: Discussionsupporting
confidence: 91%
“…However, recent studies have highlighted the role of the RAS/RAF/ERK (MAPK) pathway in the pathogenesis of several histiocytic disorders, although few cases of RDD have been evaluated [5][6][7][8][9]31]. The RAS/RAF/ERK (MAPK) pathway is involved in various cellular functions including cellular proliferation, differentiation, and migration; mutation of genes involved in this pathway has been implicated in oncogenesis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Rare mutations in other MAPK pathway members including ARAF and MAP3K1 have also been reported. 39,40 Finally, mutations affecting other signaling pathway such as PIK3CA, PICK1, and PICK3R2 have also been described in LCH. 37,41 The presence of BRAF mutations has been investigated in nonLCHs.…”
mentioning
confidence: 99%
“…Targeted sequencing studies identified MAP2K1 mutations in 15%-50% of cases with wild-type BRAF (Figure 2). 20,21 Another WES study of 3 LCH cases revealed 1 lesion with BRAF-V600E, 1 with a complex somatic activating mutation in ARAF, and 1 without MAPK gene mutations identified. As in our series, Nelson et al also described a very low overall rate of somatic mutations.…”
Section: Molecular Landscape Of Lch: Mapk Activationmentioning
confidence: 99%
“…23 Recurrent loss-of-function mutations in MAP3K1, encoding MEKK1 (which primarily impacts JNK signaling but also interacts with MAPK pathway) that are not exclusive to BRAF have also been described in a targeted sequencing approach in 3/30 LCH cases, but were not detected in our WES study of 41 LCH lesions. 21 Larger series will be required to determine the frequency and functional significance of recurrent mutations in pathways outside of MAPK signaling. The role of acquired modifying mutations or development of subclonal populations also requires further investigation.…”
Section: Molecular Landscape Of Lch: Mapk Activationmentioning
confidence: 99%